Sintering properties of zirconia-based ceramic composite. (8th December 2014) - Chew, W. J. Kelvin; Ramesh, S.; Wong, Y. H.; Misran, H.; Yusuf, F.; Tan, C. Y.; Amiriyan, M.; Tolouei, R.; Teng, W. D.
<x content-type="archive" xml:space="preserve">Abstract</x> This study examines the effects of different ZrB2 content on various mechanical properties and electrical conductivity of ZrB2/Y-TZP composite. Composites with ZrB2 content of up to 20 wt-% were particularly beneficial at the lower sintering temperature range by achieving greater densification and better hardness than Y-TZP monolith. In contrast to the trends estimated from rule of mixture, the increment of ZrB2 content did not result in any significant improvement in the elastic modulus and hardness of the zirconia composites. Nevertheless, all composites showed tremendous improvement in fracture toughness compared with monolithic Y-TZP and thus, suggested that other toughening mechanisms were operative besides transformation toughening of zirconia. Incorporation of ZrB2 up to mass fraction of 20 wt-% into Y-TZP generally did not affect the tetragonal phase stability of zirconia. Significant reduction of electrical resistivity of the composites was achieved with ZrB2 content of 20 wt-% and sintering temperature of 1400°C.